PERAN KOMUNIKASI ANTARA IBU DALAM MENGATASI MASALAH KESEHATAN MENTAL REMAJA DI LINGKUNGAN PERUMAHAN GRAHA MITRA CITRA - Syahla Nabilla Putri (Cahaya Ilmu Bangsa, 2025)
This reserch aims to find out more about the role of communication between mother in overcoming mental health problems, especially among adolescents. Mental health is defined as the development of both intellectual and physical well-being, and plays a significant role in their growth process. Adolescents who are in the growth and development phase are very vulnerable to depression, anxienty, and behavioral disorders. This research applied descriptive qualitative method, with data collection through interview and literature study. The results of the interview prove that mental health problems among adolescents are a serious problem, especially the resulting impact of emotional instability can cause adolescents to hurt themselves and others, and it’s not easy to share stories with the mother about the problems they are facing. This study proves that the role of a mother is indispensable in the continuity of mental recovery by condutcting effective communication. The results of this study provide greater insight for mothers to pay more anttention, and support mental health in adolescencts.